2019
DOI: 10.3389/fpsyg.2019.01818
|View full text |Cite
|
Sign up to set email alerts
|

Medically Unexplained Symptoms and Attachment Theory: The BodyMind Approach®

Abstract: This article discusses how The BodyMind Approach® (TBMA) addresses insecure attachment styles in medically unexplained symptoms (MUS). Insecure attachment styles are associated with adverse childhood experiences (ACEs) and MUS (Adshead and Guthrie, 2015) and affect sufferers’ capacity to self-manage. The article goes on to make a new hypothesis to account for TBMA’s effectiveness (Payne and Brooks, 2017), that is, it addresses insecure attachment styles, which may be present in some MUS sufferers, leading to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 67 publications
0
14
0
Order By: Relevance
“…Future research may also attempt to answer questions present in the DMT literature (Koch et al, 2019): what do DMT and mindfulness-based interventions have in common? Additional mindfulness principles that have been incorporated in DMT through the practice of authentic movement, such as the concept of bodymindfulness (Payne and Brooks, 2019) or "bodyfulness" (Caldwell, 2014), can be further considered in future research studies.…”
Section: Discussionmentioning
confidence: 99%
“…Future research may also attempt to answer questions present in the DMT literature (Koch et al, 2019): what do DMT and mindfulness-based interventions have in common? Additional mindfulness principles that have been incorporated in DMT through the practice of authentic movement, such as the concept of bodymindfulness (Payne and Brooks, 2019) or "bodyfulness" (Caldwell, 2014), can be further considered in future research studies.…”
Section: Discussionmentioning
confidence: 99%
“…In TBMA groups, “safety” is fundamental, and the program is designed with that in mind ( Payne and Brooks, 2019 ) because insecure attachment has been associated with MUS patients ( Adshead and Guthrie, 2015 ). A positive perception of the group can indicate that members view the group as trustworthy and safe to explore and practice new skills ( Kivlighan and Tarrant, 2001 ).…”
Section: Discussionmentioning
confidence: 99%
“…The BodyMind Approach ® was first researched in 2004 ( Payne, 2009a , b ; Payne and Stott, 2010 ) which showed promising outcomes. Further research with larger numbers demonstrated that TBMA increased wellbeing and activity levels, and decreased depression, symptom distress, and anxiety ( Payne and Brooks, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This model which will be the basis of all future interactions with others and formation of his or her attachment type, and has a particular role in processing emotional situations and acquiring emotional responses. [ 9 10 ] In other words, the process of normal emotional processing in the face of stressful situations requires the search for safe sources as real or internalized patterns of attachment. [ 11 ] Various studies have not only demonstrated the existence of a difficult transition period such as high levels of emotional abuse and neglect[ 12 ] in patients with somatic symptoms but also identified the presence of insecure attachment in these patients as a general symptom.…”
Section: Introductionmentioning
confidence: 99%